Subaltern Sovereigns Rituals of Rule and Regeneration in Highland Odisha, India - Berger, Peter (Religion and Society, 2023)
Through an ethnographic and comparative study of rituals in a "tribal" region of Odisha, this book, in its core, deals with indigenous conceptualizations of sovereignty. The local proverb that connects the ritual of the king with those of his subjects epitomizes the idea of shared sovereignty that hinges sacrificial co-responsibility in navigating the flow of life.